Composite anion exchange membrane and preparation method thereof
By introducing polyphenol and piperidine functional group modifications on ZIF-8 and combining with PTPip polymer, the problems of filler compatibility and uneven distribution in the composite anion exchange membrane were solved, and a composite membrane with high ion conductivity and long-term stability was achieved.
Patent Information
- Application Number
- CN202411892395.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
During the preparation process, the existing composite anion exchange membrane has problems such as poor compatibility between fillers and polymers, uneven distribution of fillers and long-term stability, which limits its performance in the field of electrochemical energy conversion.
By introducing a polyphenol-containing tanninic acid bonding medium and a flexible long side chain with piperidine functional groups on the alkali-stable ZIF-8, a modified metal organic frame was formed, and combined with a highly alkali-stable PTPip polymer, a composite anion exchange membrane with excellent compatibility and uniform filler distribution was prepared.
Excellent compatibility between filler and polymer is achieved, uniform dispersion of filler is ensured, the ion conductivity and long-term stability of the membrane are significantly improved, and the comprehensive performance of the composite anion exchange membrane is improved.
Smart Images

Figure CN119633615A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of membrane technology, and in particular to a composite anion exchange membrane and a preparation method thereof. Background Art
[0002] Anion exchange membrane water electrolysis (AEMWEs) is an emerging energy conversion technology that uses anion exchange membranes as solid electrolyte membranes to achieve hydrogen production from water electrolysis, and has great potential in "hydrogen production". Among them, anion exchange membranes (AEMs), as the core material of AEMWEs, play the dual role of charge carriers and electrical / gas barriers. These membranes not only ensure the efficient flow of charged ions, but also play an indispensable role in preventing the cross-penetration of electrolytes, which greatly affects the efficiency and reaction rate of hydrogen production from water electrolysis.
[0003] AEMs are composed of a polymer skeleton, fixed cationic groups, and free anions (such as OH-) that balance the charge of the cationic groups. In practical applications, how to simultaneously achieve high ionic conductivity, high dimensional stability, and excellent chemical stability has become a major challenge in the development of new AEMs.
[0004] In order to improve the above performance, in existing research, it is a common practice to introduce advanced fillers to prepare composite AEMs. For example, the invention patent with publication number CN118431526A reports an organic-organic hybrid anion exchange membrane, which is cross-linked with organic nanotubes by PTP-FM-N copolymer to form a series of composite membranes. However, the prior art still has some defects in the preparation of composite AEMs, mainly including poor compatibility between fillers and polymer matrices, uneven distribution of fillers in the membrane, and gradual decrease in membrane stability during long-term use. These problems limit the performance of AEMs in the field of electrochemical energy conversion. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present invention aims to provide a composite anion exchange membrane, which has excellent compatibility between the filler and the polymer, can ensure that the filler is evenly distributed in the membrane, has high ion conductivity and good long-term stability.
[0006] The second aspect of the present invention aims to provide a method for preparing a composite anion exchange membrane.
[0007] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions: According to the purpose of the first aspect of the present invention, the present invention provides a composite anion exchange membrane, characterized in that it includes a modified metal-organic framework and a quaternized polyterphenylpiperidine (PTPip) polymer composited with the modified metal-organic framework; wherein the modified metal-organic framework includes a metal-organic framework (MOF) having a bonding medium containing polyphenols introduced onto the surface and grafted with flexible long side chains with piperidine functional groups.
[0008] Preferably, the polyphenol-containing binding medium comprises tannic acid (TA).
[0009] Preferably, the flexible long side chain with a piperidine functional group comprises 4-(6-bromohexyl)-1,1-dimethylpiperidin-1-ium (6Brpip).
[0010] Preferably, the metal organic framework comprises a zeolitic imidazolate framework (ZIF-8).
[0011] The presence of piperidinium cations on the flexible long side chains increases the ion exchange capacity of the composite membrane, making the hydrophilic domains on the membrane more obvious, thereby greatly improving the overall performance of the membrane. In the present application, by attaching flexible long side chains with piperidine functional groups to alkaline-stable ZIF-8, the piperidinium cation density of the filler is very high, promoting the free exchange of OH- ions, and significantly improving the ion conductivity of the membrane. This improved method enhances the compatibility between the filler and the polymer, is conducive to the uniform dispersion of the filler, thereby improving the comprehensive performance of the prepared AEM.
[0012] According to the purpose of the second aspect of the present invention, the present invention also provides a method for preparing the composite anion exchange membrane as described above, characterized in that it comprises the following steps: S1. Modification of metal organic framework by binding medium: the metal organic framework is dispersed in deionized water, a binding medium containing polyphenol is added thereto, the mixture is allowed to stand, centrifuged and washed to obtain product A; S2. Flexible long side chain modified product A: dissolving product A and a flexible long side chain with a piperidine functional group in a solvent, adding a strong alkaline auxiliary agent after complete dissolution, centrifuging, washing and drying to obtain product B; S3. Preparation of composite anion exchange membrane: dissolve the quaternized polyterphenyl piperidine polymer in a solvent, stir and disperse it, then add product B, mix evenly to obtain a mixed solution, prepare an anion exchange membrane from the mixed solution by a solution casting method, and vacuum dry the anion exchange membrane to obtain a composite anion exchange membrane.
[0013] Preferably, in step S1, the metal organic framework is prepared by the following steps: at room temperature, take a clean beaker, add 2-methylimidazole, dissolve it with methanol, and mark it as solution A. In another container, use methanol to dissolve a certain amount of zinc salt, which is marked as solution B. Quickly pour solution B into solution A, stir, add a certain amount of sodium borohydride, stir, centrifuge, wash with ethanol, and dry the obtained solid to obtain ZIF-8.
[0014] Preferably, in the solution A, the ratio of 2-methylimidazole to methanol is (32-33) g: (100-400) ml.
[0015] Preferably, in the solution B, the ratio of zinc salt to methanol is (14-15) g: (50-200) ml.
[0016] Preferably, in step S1, the volume of deionized water is 5-10 mL.
[0017] Preferably, in step S1, the ratio of the metal organic framework to the binding medium containing polyphenol is (8-12) g: (1-5) mg.
[0018] Preferably, in step S1, the standing time is 3 to 6 minutes.
[0019] Preferably, in step S2, the flexible long side chain with a piperidine functional group is prepared by the following steps: 1,6-dibromohexane is added to ethyl acetate in a single-necked flask, and stirred to prepare solution C. N-methylpiperidine is poured into ethyl acetate in a beaker, and stirred to prepare solution D. Solution D is slowly added dropwise to solution C and mixed evenly, and reacted for 24 hours to generate a large amount of white precipitate. The reactant is allowed to stand for 10 minutes, and the supernatant is discarded, and the collected solid is repeatedly washed with ethyl acetate to obtain the product 6Brpip.
[0020] Preferably, in the solution C, the ratio of 1,6-dibromohexane to ethyl acetate is (0.15-0.25) mol: (130-160) mL.
[0021] Preferably, in the solution D, the ratio of N-methylpiperidine to ethyl acetate is (0.05-0.15) mol: (40-70) mL.
[0022] Preferably, in step S2, the strong alkaline auxiliary agent includes potassium carbonate.
[0023] Preferably, in step S2, the ratio of product A to the flexible long side chain with a piperidine functional group is (80-100) mg: (280-320) mg.
[0024] Preferably, in step S2, the solvent includes N,N-dimethylformamide (DMF).
[0025] Preferably, in step S2, the ratio of the strong alkaline auxiliary agent to the flexible long side chain with a piperidine functional group is (20-35) mg:(80-320) mg.
[0026] Preferably, in step S3, the quaternized polyterphenyl piperidine polymer is prepared by the following steps: adding polyterphenyl piperidine (PTP), iodomethane, dimethyl sulfoxide and 1-methyl-2-pyrrolidone into a container, shielding the container from light, stirring, precipitating in ether, washing several times, filtering and drying to obtain the quaternized polyterphenyl piperidine polymer.
[0027] Preferably, the ratio of PTP to methyl iodide is (1-1.5) g: (0.4-1) mL.
[0028] Preferably, the ratio of dimethyl sulfoxide to 1-methyl-2-pyrrolidone is (10-15) mL: (40-60) mL.
[0029] Further preferably, the PTP is prepared by the following steps: N-methyl-4-piperidone, p-terphenyl and dichloromethane are added to a three-necked flask equipped with a mechanical stirrer. After complete dissolution, trifluoroacetic acid and trifluoromethanesulfonic acid are added dropwise. After a certain reaction time, the viscous solution is poured into a sodium bicarbonate solution and stirred vigorously, and finally a white fibrous product is obtained after filtering and washing, and a PTP polymer is obtained by vacuum drying.
[0030] Preferably, the ratio of N-methyl-4-piperidone to p-terphenyl is (50-60) mmol: (40-50) mmol.
[0031] Preferably, the volume of dichloromethane is 15-30 mL.
[0032] Preferably, the ratio of trifluoroacetic acid to trifluoromethanesulfonic acid is (2-5) mL: (20-40) mL.
[0033] Preferably, the concentration of the sodium bicarbonate solution is 1 to 3 mol / L.
[0034] Preferably, the polymerization temperature is 0°C.
[0035] Preferably, the polymerization time is 8 to 14 hours.
[0036] Preferably, in step S3, the solvent includes dimethyl sulfoxide. Further preferably, the ratio of PTPip to dimethyl sulfoxide is (0.1-0.4) g: (6-15) mL.
[0037] Preferably, in step S3, the ratio of product B to PTPip is (1-40) mg: (0.1-0.4) g.
[0038] Preferably, in step S3, the anion exchange membrane is vacuum dried at a temperature of 60-80°C.
[0039] The beneficial effects of the present invention are: 1. The composite anion exchange membrane provided by the present invention is prepared by introducing a tannic acid bonding medium containing polyphenols on the surface of alkaline stable ZIF-8, then introducing a flexible long side chain with a piperidine functional group, and then combining the modified ZIF-8 functional cluster with a highly alkaline stable PTPip polymer. The filler and the polymer have excellent compatibility, which is conducive to the uniform dispersion of the filler, thereby showing higher ion conductivity and good long-term stability.
[0040] 2. Since both Pip-TA@ZIF-8 filler and PTPip are soluble in common organic solvents, the present invention adopts a physical mixing and stirring method for doping. This preparation method has the advantage of simple process and a yield of up to 85%. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The conductivity curve images of the anion exchange membranes prepared in Examples 1-3 of the present invention and Comparative Example 1 are as a function of temperature; Figure 2 The water absorption images of the anion exchange membranes prepared in Examples 1-3 of the present invention and Comparative Example 1 at different temperatures; Figure 3 The swelling rate images of the anion exchange membranes prepared in Examples 1-3 of the present invention and Comparative Example 1 at different temperatures; Figure 4 The mechanical properties images of the anion exchange membranes prepared in Examples 1-3 of the present invention and Comparative Example 1; Figure 5 The performance images of hydrogen production by water electrolysis of the anion exchange membranes prepared in Examples 1-3 of the present invention and Comparative Example 1 and FAA-3-50. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0043] Example 1 1. Synthesis and preparation of ZIF-8 At room temperature, take a clean beaker and dissolve 2-methylimidazole (300 mg) in 40 mL of methanol, labeled as solution A. In another clean beaker, dissolve Zn(NO 3 ) 2 -6H 2 O (650 mg) was dissolved in 40 mL of methanol and labeled as solution B. Solution B was quickly poured into solution A and stirred for 5 min, then 200 mg of NaBH was slowly added using a microprobe. 4 , and stirred for 10 min. Finally, the white product was centrifuged and washed with ethanol. ZIF-8 powder was dried and activated at 100 °C overnight before use.
[0044] 2. Synthesis and preparation of 6BrPip In a single-necked flask, 1,6-dibromohexane was added to ethyl acetate and stirred evenly to prepare solution C. In a beaker, N-methylpiperidine was poured into ethyl acetate and stirred evenly to prepare solution D. Solution D was slowly added dropwise to solution C and mixed evenly. The mixture was reacted for 24 hours to generate a large amount of white precipitate. The reactants were allowed to stand for 10 minutes, and the supernatant was discarded. The collected solids were repeatedly washed with ethyl acetate to obtain the product 6Brpip.
[0045] 3. Synthesis and preparation of PTPip polymer PTP (1 g), iodomethane (2.28 g, 15.6 mmol), dimethyl sulfoxide (5 mL) and 1-methyl-2-pyrrolidone (25 mL) were added to a single-necked flask and shielded from light with a light shield. After stirring at 80 °C for 24 hours, the mixture was precipitated in ether and then washed several times with deionized water. After filtration, the mixture was dried in a vacuum oven at 60 °C for 24 hours to obtain the PTPip polymer.
[0046] Among them, PTP was prepared by the following steps: N-methyl-4-piperidone (6.44 g, 57 mmol), p-terphenyl (10.1 g, 43.8 mmol) and dichloromethane (20 mL) were added to a three-necked flask equipped with a mechanical stirrer. After complete dissolution, trifluoroacetic acid (3 mL) and trifluoromethanesulfonic acid (30 mL) were added dropwise. After a certain reaction time, the viscous solution was poured into a sodium bicarbonate solution (1 mol / L, 1000 mL) and stirred vigorously. Finally, a white fibrous product was obtained after filtration and washing. The polymer was dried in a vacuum oven at 60 °C for 24 hours to obtain a PTP polymer.
[0047] 4. Synthesis and preparation of composite anion exchange membrane S1. Synthesis of TA-modified ZIF-8 (TA@ZIF-8): ZIF-8 (10 mg) was dispersed in 5 mL of deionized water. Then, 2 mL of tannic acid solution (10 g / L) was added to the ZIF-8 suspension and allowed to stand for 5 min. After centrifugation and washing with water, TA@ZIF-8 was obtained.
[0048] S2.6BrPip side chain modified TA@ZIF-8 (Pip-TA@ZIF-8) synthesis: TA@ZIF-8 (100 mg) and 6Br-Pip (300 mg) were dissolved in 60 mL N,N-dimethylformamide. After complete dissolution, potassium carbonate (24 mg) was added and stirred for 48 h. Finally, the gray-green product was centrifuged, washed with water, and dried at 100 °C.
[0049] S3. Preparation of PTPip-1 composite anion exchange membrane: PTPip (0.2 g) was dissolved in dimethyl sulfoxide and stirred at room temperature for 24 h. Pip-TA@ZIF-8 (0.002 g) was then added and the mixture was ultrasonically treated for 48 h to obtain a uniform solution. An anion exchange membrane was prepared on a glass plate by solution casting, and the anion exchange membrane was placed in a vacuum oven at 80 °C to dry to obtain a PTPip-1 composite anion exchange membrane.
[0050] Example 2 This example is basically the same as Example 1, except that PTPip (0.2 g) was dissolved in dimethyl sulfoxide and stirred at room temperature for 24 hours. Pip-TA@ZIF-8 (0.01 g) was added, and the mixture was ultrasonically treated for 48 hours to obtain a uniform solution. The exchange membrane was prepared on a glass plate by a solution casting method, and the exchange membrane was placed in a vacuum oven at 80°C to dry to obtain a PTPip-5 composite anion exchange membrane.
[0051] Example 3 This example is basically the same as Example 1, except that PTPip (0.2 g) was dissolved in dimethyl sulfoxide and stirred at room temperature for 24 hours. Pip-TA@ZIF-8 (0.018 g) was added, and the mixture was ultrasonically treated for 48 hours to obtain a uniform solution. The exchange membrane was prepared on a glass plate by solution casting, and the exchange membrane was placed in a vacuum oven at 80°C to dry to obtain a PTPip-9 composite anion exchange membrane.
[0052] Comparative Example 1 This comparative example is basically the same as Example 1, except that PTPip (0.2 g) was dissolved in dimethyl sulfoxide and stirred at room temperature for 24 hours. The polymer solution was then ultrasonically treated for 48 hours to obtain a uniform solution. A membrane was prepared on a glass plate by a solution casting method, and the mixed membrane was placed in a vacuum oven at 80°C and dried to obtain a PTPip anion exchange membrane.
[0053] Experimental Testing The conductivity curves of Examples 1-3 and Comparative Example 1 as a function of temperature are shown in the attached figure. Figure 1 The conductivity, i.e., the in-plane OH-conductivity, was measured by AC impedance spectroscopy in the frequency range of 0.1 Hz to 1 MHz using an Autolab (AUT86925) electrochemical workstation using a four-electrode probe method. The membrane was cut into rectangular pieces (40 × 10 mm 2 ), the tests were conducted at different temperatures, the experiments were tested in water and exposed to air. The conductivity (σ) is calculated as follows: σ = L / RS, where L is the distance between the two electrodes, R is the resistance of the membrane, and S is the cross-sectional area of the membrane.
[0054] Depend on Figure 1 It can be seen that the filler Pip-TA@ZIF-8 significantly improves the conductivity of PTPip, and the anion exchange membrane provided in the present application has a relatively high conductivity. Among them, PTPip-1 obtained in Example 1 is the embodiment with the highest conductivity.
[0055] The water absorption rate (WU) and expansion rate (SR) of Examples 1-3 and Comparative Example 1 are shown in the attached figure. Figure 2 and attached Figure 3 , water absorption and expansion rate test method: the film is in OH- form, weigh the weight of the dry film (W dry ) and thickness (L dry Subsequently, the dried membrane was immersed in deionized water at different temperatures (30-80 °C) for 24 h to fully hydrate it. The excess water on the membrane surface was then wiped off with filter paper, and the weight of the fully hydrated membrane (W wet ) and thickness (L wet ). The calculation formulas of WU and SR are as follows: WU (%) = (W wet -W dry ) / W dry × 100%, SR (%) = (L wet -L dry ) / L dry ×100%.
[0056] Depend on Figure 2 and Figure 3It can be seen that the Pip-TA@ZIF-8 filler improves the water absorption and swelling rate of PTPip. The composite membranes obtained in Examples 1-3 all maintain a certain swelling rate and good water absorption rate, providing certain conditions for the dimensional stability of the membrane. Among them, PTPip-1 obtained in Example 1 still exhibits good water absorption at 80°C (17.7%, see Figure 2 ) and anti-swelling (<8%, see Figure 3 ).
[0057] The mechanical properties of the anion exchange membranes of Examples 1-3 and Comparative Example 1 are summarized as follows: Figure 4 . Mechanical properties test method of anion exchange membrane: The tensile modulus of the sample was evaluated using a tensile tester (Instron 5965) at a tensile rate of 1 mm / min at room temperature. The sample was cut into 5 mm × 5 cm strips before testing, and the sample was immersed in deionized water for storage. Before the test, the moisture on the membrane surface was wiped off. Each sample was tested 5 times under the same test conditions for analysis.
[0058] Depend on Figure 4 It can be seen that the composite anion exchange membrane prepared in the present application has a good Young's modulus performance. Among them, PTPip-1 obtained in Example 1 is the embodiment with the best mechanical properties among Examples 1-3.
[0059] The performance diagrams of water electrolysis hydrogen production of Examples 1-3, Comparative Example 1 and FAA-3-50 are summarized as follows: Figure 5 , where FAA-3-50 is a commonly used commercial anion exchange membrane. The assembled membrane electrode is assembled from NiFe catalyst, PTPip-1 and Pt / C catalyst. NiFe or Pt / C catalyst is uniformly mixed with 20wt% FAA-3-50 ion polymer in isopropanol / DI water (1:1) solution. After being fully dispersed, the ink is sprayed on the fluid collector (4 cm 2 ; anode, nickel foam; cathode, carbon paper diffusion layer). Catalyst loading: NiFe 5.0 mg / cm 2 , Pt / C 0.4 mg / cm 2 The performance of AEMWE based on Examples 1-3 and Comparative Example 1 in 1 M KOH solution and pure water was studied. Polarization curves in the temperature range of 50-80°C and the voltage range of 0-2.0 V were recorded using a NEWWAR battery test station.
[0060] Depend on Figure 5It can be seen that the Pip-TA@ZIF-8 filler improves the alkaline water electrolysis hydrogen production performance of PTPip. The electrolysis performance of the PTPip-1 membrane water obtained in Example 1 was significantly improved, achieving a stable high energy input (2.31 A / cm at 2 V). 2 ).
Claims
1. A composite anion exchange membrane, characterized in that: The invention comprises a modified metal organic framework and a quaternized polyterphenyl piperidine polymer compounded with the modified metal organic framework; wherein the modified metal organic framework comprises a metal organic framework with a bonding medium containing polyphenol introduced on the surface and a flexible long side chain with piperidine functional groups grafted thereon.
2. The composite anion exchange membrane according to claim 1, characterized in that: The polyphenol-containing binding medium includes tannic acid.
3. The composite anion exchange membrane according to claim 1, characterized in that: The flexible long side chain with a piperidine functional group includes 4-(6-bromohexyl)-1,1-dimethylpiperidin-1-ium.
4. The composite anion exchange membrane according to claim 1, characterized in that: The metal organic framework comprises a zeolite imidazole framework.
5. A method for preparing a composite anion exchange membrane according to any one of claims 1 to 4, characterized in that: The steps include: S1. Modification of metal organic framework by binding medium: the metal organic framework is dispersed in deionized water, a binding medium containing polyphenol is added thereto, the mixture is allowed to stand, centrifuged and washed to obtain product A; S2. Flexible long side chain modified product A: dissolving product A and a flexible long side chain with a piperidine functional group in a solvent, adding a strong alkaline auxiliary agent after complete dissolution, centrifuging, washing and drying to obtain product B; S3. Preparation of composite anion exchange membrane: dissolve the quaternized polyterphenyl piperidine polymer in a solvent, stir and disperse it, then add product B, mix evenly to obtain a mixed solution, prepare an anion exchange membrane by solution casting, and vacuum dry the anion exchange membrane to obtain a composite anion exchange membrane.
6. The method for preparing a composite anion exchange membrane according to claim 5, characterized in that: In the step S2, the strong alkaline auxiliary agent includes potassium carbonate.
7. The method for preparing a composite anion exchange membrane according to claim 5, characterized in that: In the step S2, the ratio of product A to the flexible long side chain with a piperidine functional group is (80-100) mg: (280-320) mg.
8. The method for preparing a composite anion exchange membrane according to claim 5, characterized in that: In step S3, the quaternized polyterphenyl piperidine polymer is prepared by the following steps: adding polyterphenyl piperidine, iodomethane, dimethyl sulfoxide and 1-methyl-2-pyrrolidone into a container, shielding the container from light, stirring, precipitating in ether, washing several times, filtering and drying to obtain a quaternized polyterphenyl piperidine polymer.
9. The method for preparing a composite anion exchange membrane according to claim 5, characterized in that: In the step S3, the ratio of product B to quaternized polyterphenyl piperidine polymer is (1-40) mg: (0.1-0.4) g.
10. The method for preparing a composite anion exchange membrane according to claim 5, characterized in that: In step S3, the anion exchange membrane is vacuum dried at a temperature of 60 to 80°C.
Citation Information
Patent Citations
Organic-organic hybrid anion exchange membrane, preparation method and application
CN118431526A
Branched polyaryl piperidine polymer and anion exchange membrane
CN115521445A
Composite enhanced anion exchange membrane as well as preparation method and application thereof
CN116742081A
Side chain modified polybiphenyl piperidine anion exchange membrane as well as preparation method and application thereof
CN118374002A